O romance detetivesco Bellini e os espíritos, de Tony Bellotto: a cena da enunciação e a presença da femme fatale - Costa, Bruno César (2019)
This research aims to studythe enunciation scene of the detective braziliannovel Bellini e os espíritos(2005), by Toni Bellotto, in order to focus on the detective-femme fatale pair inits correlationwith the genre tradition, especially The FalconMaltese (1930), by Dashiell Hammett in American Literature. To this end, a historical research was conducted about the emergence of the American detective literature -its discourse, protagonists and readers-, as well asthe insertion of the genre in the Brazilian Literature. We have evidenced the existence of two variations of the detective literature: the classic one, that has for example the tales of Edgar Allan Poe, and the hard-boiledones, that became a reference in diverse artistic means, especially the cinematic one. As theoretical foundations, we selected the studies present in Wayne Booth's publication The Rhetoric of Fiction (1980) and the discursive strategies of showing and telling in their relationship with the narrator. The analysis used similarities and differences between the detective-femme fatale pair in Bellini e os espíritos and Hammett’s The Maltese Falcon to better understand and highlight how Bellotto appropriated the concepts inherent in gender in the conception of his Brazilian narrative